Mitochondrial dynamics at the intersection of macrophage polarization and metabolism - Li, Pan; Fan, Zhengbo; Huang, Yanlan; Luo, Liang; Wu, Xiaoyan (Frontiers in Immunology, 2025)
Macrophages are vital sentinels in innate immunity, and their functions cannot be performed without internal metabolic reprogramming. Mitochondrial dynamics, especially mitochondrial fusion and fission, contributes to the maintenance of mitochondrial homeostasis. The link between mitochondrial dynamics and macrophages in the past has focused on the immune function of macrophages. We innovatively summarize and propose a link between mitochondrial dynamics and macrophage metabolism. Among them, fusion-related FAM73b, MTCH2, SLP-2 (Stomatin-like protein 2), and mtSIRT, and fission-related Fis1 and MTP18 may be the link between mitochondrial dynamics and macrophage metabolism association. Furthermore, post-translational modifications (PTMs) of mtSIRT play prominent roles in mitochondrial dynamics-macrophage metabolism connection, such as deacetylates and hypersuccinylation. MicroRNAs such as miR-150, miR-15b, and miR-125b are also possible entry points. The metabolic reprogramming of macrophages through the regulation of mitochondrial dynamics helps improve their adaptability and resistance to adverse environments and provides therapeutic possibilities for various diseases.